EVALUASI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA RUMAH MAKAN LESEHAN DI MUARA TEWEH - Liawati (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2026)
The purpose of this study was to describe service quality based on the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, as well as to determine the level of customer satisfaction and the relationship between service quality and customer satisfaction at a lesehan restaurant in Muara Teweh. This study used a descriptive qualitative approach with customers of the lesehan restaurant in Muara Teweh as research subjects. The informants consisted of 8 customers selected using purposive sampling because they were considered capable of providing in-depth information based on direct experience. Data were collected through interviews, observations, documentation, and literature study. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that service quality at the lesehan restaurant in Muara Teweh was generally quite good in all SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. Customers assessed that cleanliness, facilities, order accuracy, service speed, employee attitude, and attention to customers were adequate. Customer satisfaction was also categorized as fairly good, indicated by expectation fulfillment, intention to revisit, and willingness to recommend to others. The findings indicate that service quality has a close relationship with customer satisfaction, where good service increases customer comfort, trust, and positive experience.